Does the timing of aspirin administration influence its antiplatelet effect – review of literature on chronotherapy - Miciak-Ławicka, Ewa; Begier-Krasińska, Beata; Tykarski, Andrzej; Krasiński, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2018)
This publication is a summary of the multidirectional effects of aspirin and its role in modern medicine. The history of aspirin, or acetylsalicylic acid (ASA), and its use dates back to ancient times, although the substance in its pure form has been produced and sold since 1899. Initially it was used for its antipyretic, analgesic, and anti-inflammatory effects. Over the years many other benefits associated with the administration of ASA have been revealed. The mechanism of aspirin’s action was discovered thanks to the British pharmacologist and Nobel Prize winner Sir John Vane. Understanding the effects of acetylsalicylic acid, associated with the inhibition of cyclooxygenase and proinflammatory thromboxane A2 and with increased concentration of vasoprotective, antithrombotic prostacyclin, gave rise to the era of using small “cardiac” doses of ASA in cardiovascular diseases. In addition to the well-researched antiplatelet effect, other properties of ASA have been discovered, such as the non-COX-1 dependent improvement of endothelial function or the hypotensive effect after evening administration. According to the currently available knowledge, it is possible to speak of a pleiotropic effect of ASA and its use in the prevention of cardiovascular diseases, taking into account its anti-aggregation effect, circadian rhythms, and the principles of chronotherapy.